(untitled) (Archaeologia Adriatica, 2013)
Among the honorifics used in the municipal sphere, those borne by college members in charge of maintaining and carrying out the duties of the imperial cult and erecting monuments pro salute et reditu imperatoris are worthy of attention. These well known colleges consisted of six members (VI viri) and were in charge of the official imperial cult. The oldest of them was the college of sevir Iulialis, recorded on a monument in Zadar (VI vir Iulialis), which in all probability preceded the later colleges associated with the cult of deified emperors. The existence of the college in Zadar is confirmed by an inscription unearthed in the course of the 1949 archaeological campaign at the Zadar Forum. The monument was erected to the seven-year-old Lucius Tettius Epidianus by his father Lucius Tettius Sperches VI vir Iulialis. The Greek cognomen and the performance of the office of sevirate define him as a freedman from the Italic Tettius family. The location for erecting a monument to his deceased seven-year-old son was allocated to Sperches by a decurion’s decree, suggesting the great personal respect which he had gained. This is the first occurrence of the title VI vir Iulialis in epigraphy. On this occasion, I shall try to analyse and explain my understandingof the appearance of this college in Iader.